Pengaruh Pemanfaatan Tepung Daun Kelor terhadap Kualitas Interior dan Kandungan Protein Telur Ayam Kampung Unggul Balitbangtan : The Effect of Moringa Leaf Flour Utilization on Interior Quality and Protein Content of Balitbangtan Superior Native Chicken Eggs - Aurelia Putri Domingga; Agustinus Konda Malik; N.G.A Mulyantini, S.S. (Universitas Nusa Cendana, 2022)
The study was conducted to evaluate the usage of moringa (Moringa oleifera) leaf flour in the ration against the interior quality and protein content of eggs in superior native chickens aged 32 weeks. Experimental design used is Complete Randomized Design with four treatments and six replications. Each experimental unit has four superior native chicken Eggs. Treatment feeds were distinguished by the percentage of use of moringa oleifera leaf flour: R0=0%, R1=5%, R2=10% and R3=15%. The results showed that the use of moringa leaf flour up to 15% in the ration can have an influence on increasing egg yolk color 63.86% and protein content 54.35%, but does not affect egg yolk index, egg white index, and haugh egg unit. Based on the results of the study, It can be concluded that increaseing in the level of moringa leaf flour from 0% to 15% in the ration can increase egg yolk color. The usage moringa leaf flour 5% to 10% in the ration can increase the protein content of eggs. Penelitian ini bertujuan untuk mengevaluasi pemanfaatan tepung daun kelor (Moringa oleifera) dalam ransum terhadap kualitas interior dan kandungan protein telur pada ayam ayam kampung unggul Balitbangtan umur 32 minggu. Penelitian ini menggunakan metode Rancangan Acak Lengkap dengan empat jenis perlakuan dan enam ulangan. Setiap unit percobaan terdapat empat ekor ayam. Pakan perlakuan dibedakan berdasarkan persentase penggunaan tepung daun kelor: R0=0%, R1=5%, R2=10% dan R3=15%. Hasil penelitian menunjukkan bahwa penggunaan tepung daun kelor sampai dengan 15% dalam ransum dapat memberikan pengaruh terhadap peningkatkan nilai warna kuning telur 63,86% dan kandungan protein sebesar 54,35%, tetapi tidak mempengaruhi nilai indeks kuning telur, indeks putih telur dan haugh unit. Dapat disimpulkan bahwa peningkatan level tepung daun kelor dari 0% sampai 15% dalam ransum dapat meningkatkan intensitas warna kuning telur. Pemanfaatan 5% sampai 10% tepung daun kelor dalam ransum dapat meningkatkan kandungan protein telur.